Adoption processes for EDM, EDI and BIM technologies in the construction industry - Samuelson, Olle; Björk, Bo-Christer (Journal of Civil Engineering and Management, 2014)
Three strategically important uses of IT in the construction industry are management of project documents on webservers (EDM), electronic handling of orders and invoices between companies (EDI) and use of 3D models including non-geometrical attributes for integrated design and construction (BIM). The purpose of this work is to study factors that affect the decisions to implement these techniques as well as the actual adoption process. In a longitudinal survey study in the Swedish Construction Industry, the extent of use of these techniques was measured in 1998, 2000 and 2007. This paper presents a follow-up to the quantitative studies, where semi-structured interviews have been used, in a qualitative approach. The theoretical basis for the studies was informed by frameworks from IT-adoption theory. The results showed that decisions to implement these technologies are made on three different levels: individual level, company organizational level, and project organizational level. Different patterns in adoption can be explained by where decisions are mainly taken. EDM is driven from the project level, EDI mainly from the company level, and BIM is driven by individuals. The study points out that decision for implementing BIM should be taken on a higher strategic level in order to deliver intended benefits.